Acute oesophageal safety of high-power short duration with 50 W for atrial fibrillation ablation. Issue 6 (2nd February 2022) - Müller, Julian; Berkovitz, Artur; Halbfass, Philipp; Nentwich, Karin; Ene, Elena; Sonne, Kai; Simu, Gelu; Chakarov, Ivalyo; Barth, Sebastian; Waechter, Christian; Behnes, Michael; Akin, Ibrahim; et al.
Abstract: Aims: Pulmonary vein isolation (PVI) using radiofrequency (RF) ablation is an effective treatment option for patients with atrial fibrillation (AF). This study aims to investigate the safety of high-power short duration (HPSD) with emphasis on oesophageal lesions after PVI. Methods and results: Consecutive patients undergoing AF ablation with HPSD (50 W; ablation index (AI)-guided; target AI 350 for posterior wall ablation, AI 450 for anterior wall ablation) using the ThermoCool SmartTouch SF catheter were included. Patients underwent post-ablation oesophageal endoscopy to detect and categorize thermal oesophageal injury (EDEL). Occurrence and risk factors of oesophageal lesions and perforating complications were analysed. A total of 1033 patients underwent AF ablation with HPSD. Of them, 953 patients (67.6 ± 9.6 years; 58% male; 43% paroxysmal AF; 68% first PVI) underwent post-procedural oesophageal endoscopy and were included in further analyses. Median procedure time was 82.8 ± 24.4 min with ablation times of 16.1 ± 9.2 min. Thermal oesophageal injury was detected in 58 patients (6%) ( n = 29 Category 1 erosion, n = 29 Category 2 ulcerous). One patient developed oesophageal perforation (redo, 4th AF ablation). No patient died. Using multivariable regression models, increased total ablation time [odds ratio (OR) 1.029, P = 0.010] and history of stroke (OR 2.619, P = 0.033) were associated with increased incidence of EDEL after AF ablation, whereas increased body mass index was protective (OR 0.980, P = 0.022). Conclusion: Thermal oesophageal lesions occur in 6% of HPSD AF ablations. The risk for development of perforating complications seems to be low. Incidence of atrio-oesophageal fistula (0.1%) is comparable to other reported series about RF ablation approaches.